Initially disseminated pediatric high-grade midline glioma without H3 K27M alteration – a case report and literature review - Stanić Tišma, Dragana; Grujičić, Danica; Kostić, Aleksandar; Denčić Fekete, Marija; Filipović, Predrag; Popović-Vuković, Marija; Bokun, Jelena; Nikitović, Marina (Vojnosanitetski pregled, 2025)
Introduction. Pediatric high-grade gliomas (HGGs) constitute an extremely heterogeneous group of highly aggressive brain tumors. While leptomeningeal dissemination is commonly observed in patients through the course of the disease, cases with initial dissemination are rare. Case report. This paper reports the case of a 12-year-old boy diagnosed with an initially disseminated HGGs with midline localization. Despite surgical intervention and a multidisciplinary treatment approach involving craniospinal radiotherapy and chemotherapy, the patient experienced rapid neurological deterioration and disease progression, and ultimately succumbed to the disease 13 months after diagnosis. In contrast to the vast majority of similar pediatric cases documented in the literature, our patient exhibited an absence of H3 K27M alteration. To our knowledge, this is a unique presentation of a midline HGG with leptomeningeal cranial and spinal dissemination at diagnosis without the expected molecular pattern typically associated with such cases. Conclusion. This case highlights that, whether disseminated or not, pediatric HGGs have similarly poor survival outcomes with no effective treatments. It also underscores the widespread challenge of incomplete molecular profiling in these tumors. This emphasizes the urgent need for a comprehensive molecular analysis of these tumors worldwide to advance diagnosis and guide the development of personalized therapy.
Keywords: brain neoplasms; glioma; neoplasm metastasis; pediatrics; survival